2020
DOI: 10.3847/2041-8213/ab7209
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transients Originating from Thermonuclear Explosions in Helium White Dwarf Tidal Disruption Events

Abstract: We study properties of the emission from thermonuclear explosions in a helium white dwarf (WD) tidal disruption event (TDE). The helium WD is not only tidally disrupted but is detonated by the tidal compression and by succeeding shocks. We focus on the emission powered by radioactive nuclei in the unbound ejecta of the TDE debris. We consider a TDE where a 0.2 M helium WD is disrupted by a 10 2.5 M intermediate-mass black hole (IMBH). We perform hydrodynamic simulations coupled with nuclear reactions, post-pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
13
1
Order By: Relevance
“…Nevertheless, the requirements on the central engine and the ejecta mass still rule out the possibility that SN 2019bkc is a SN ".Ia" explosion due to helium-shell detonations on the surface of a sub-Chandrasekhar mass WD (Bildsten et al 2007;Shen et al 2010). Alternatively, SN 2019bkc could originate from the collapse/disruption of a WD, specifically, (i) an accretion-induced collapse of a WD (Canal & Schatzman 1976;Ergma & Tutukov 1976;Dessart et al 2006;Yu et al 2019b,c), (ii) a merger of a WD with a NS or a stellar-mass black hole (BH; Metzger 2012;McBrien et al 2019), and (iii) the tidal disruption of a WD by a BH of an intermediate mass of ∼ 10 2.5 M ⊙ (Kawana et al 2020). Fairly speaking, the last scenario could be most likely to generate a sufficiently heavy ejecta.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Nevertheless, the requirements on the central engine and the ejecta mass still rule out the possibility that SN 2019bkc is a SN ".Ia" explosion due to helium-shell detonations on the surface of a sub-Chandrasekhar mass WD (Bildsten et al 2007;Shen et al 2010). Alternatively, SN 2019bkc could originate from the collapse/disruption of a WD, specifically, (i) an accretion-induced collapse of a WD (Canal & Schatzman 1976;Ergma & Tutukov 1976;Dessart et al 2006;Yu et al 2019b,c), (ii) a merger of a WD with a NS or a stellar-mass black hole (BH; Metzger 2012;McBrien et al 2019), and (iii) the tidal disruption of a WD by a BH of an intermediate mass of ∼ 10 2.5 M ⊙ (Kawana et al 2020). Fairly speaking, the last scenario could be most likely to generate a sufficiently heavy ejecta.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Specifically, their remote locations and old host environments point to old progenitors involving white dwarfs (WDs) in binary systems. Suggested channels include helium shell detonations on WDs (Bildsten et al 2007;Shen et al 2010;Waldman et al 2011;Sim et al 2012;Dessart & Hillier 2015;Meng & Han 2015), double detonations of He shells on the surface of WDs (Sim et al 2012;Polin et al 2019aPolin et al , 2019b, mergers of WDs with neutron stars (Metzger 2012;Margalit & Metzger 2016;Bobrick et al 2017;Toonen et al 2018;Zenati et al 2019), tidal disruptions of WDs by intermediate-mass black holes (Rosswog et al 2008;MacLeod et al 2014;Sell et al 2015;MacLeod et al 2016;Sell et al 2018;Kawana et al 2020), and even extreme core-collapse SNe from highly stripped massive stars (Tauris et al 2015;Moriya et al 2017); however their old environments make core-collapse SNe unlikely (Perets et al 2011). If they arise from binary WD systems, Meng & Han (2015) show that the old environments and consequently long delay times constrain the progenitor binary to consist of low-mass CO (0.6  M ) and He (0.25  M ) WDs.…”
Section: Introductionmentioning
confidence: 99%
“…This detection rate is based on a WD TDE with a 0.6𝑀 CO WD disrupted by a 10 3 𝑀 BH. However, luminosity of a thermonuclear transient depends on WD mass (MacLeod et al 2016a;Kawana et al 2020). Moreover, the success rate of thermonuclear explosion should be sensitive to both BH and WD masses, and WD compositions (e.g.…”
Section: Detectabilitymentioning
confidence: 99%
“…There are two previous studies to investigate emission properties of such transients. MacLeod et al (2016a) have examined a TDE of a 0.6𝑀 CO WD, while Kawana et al (2020) have focused on a TDE of a 0.2𝑀 He WD. Both of them have suggested that such transients should be rapid and faint transients in optical and ultraviolet bands.…”
Section: Detectabilitymentioning
confidence: 99%
See 1 more Smart Citation